PENERAPAN METODE SIMPLEKS DALAM UPAYA MEMAKSIMALKAN PENDAPATAN - Alan Rusdiana; Deni Istiono (Jurnal Ekonomi dan Bisnis, 2023)
This study aims to calculate the maximum profit from selling Bella Bakery's white bread and donuts and to determine the use of the simplex method on raw material constraints experienced by Bella Bakery. In addition, this study utilizes the POM-QM software for windows software to estimate the maximum profit obtained from each production of white bread and donuts at Bella Bakery so that it has an accurate estimate. This research method includes problem identification, problem solving model selection, data collection, data processing and analysis, model implementation, and results evaluation. Based on the analysis results show that the simplex method can be used to determine the maximum profit at Bella Bakery. The maximum profit earned by Bella Bakery is Rp. 200,000 by producing only one type of product, namely donuts with a total of 50.1 boxes or 501 pieces. In addition, the POM-QM for windows software is very useful to help determine the maximum profit quickly, precisely and accurately.